Pendidikan Prenatal dalam Al-Qur'an (Studi Surah An-Nahl Ayat 78): Prenatal Education In the Qur'an Study of Surah An-Nahl Verse 78 - fitriyah, Lailatul fitri (Al Karima : Jurnal Studi Ilmu Al Quran dan Tafsir, 2023)
Prenatal education is very important education in child development, because prenatal education is foundation education for childrens. In the Al-Qur’an there is verse wich explain about prenatal education on of them is surah An-nahl verse 78 . In this research the writer reaserched surah an-nahl verse 78 according of the commentators of Al-Qur’an. In this research uses library reaserch and this reaserch method uses the Maudhu’I method. The purpose of this research is to knowing of explain the commentators of Al-Qur’an about prenatal education in the Qur’an Surah An-Nahl verse 78. The purpose of this research to know opinion of commentator of the Qur’an about prenatal education in the surah an-nahl verse 78. In this research the are some opinions commentator of the Qur’an, that is the first, the are commentator who think is prenatal education can occur at the stage of pregnance because senses are working and can receive stimulation from outside the womb, the second opinion, the are commentator who think is prenatal education can not happen because the senses can not working and can not receive stimulation from outside the womb, third opinion, does not link surah an-nahl verse 78 with prenatal education.